Penyuluhan Kompetensi Komunikasi Non Verbal Bagi Masyarakat di Desa Mekarmukti, Bandung Barat - Sri Seti Indriani; Ditha Prasanti (Jurnal Pengabdian Pada Masyarakat, 2017)
Non-verbal communication is the delivery of messages without words and gives meaning to verbal communication, where non-verbal communication is older than verbal communication because since we were born we have done it until the age of about 18 months, such as touch, smile, crying eyes, and so on. Without us knowing we have practiced it, it is no wonder, if we doubt someone, we are more confident in the nonverbal message (probably from his movements). This shows how important we are to learn the knowledge of non-verbal communication. This is what underlies the author performs Community Service (PKM) with the title "Communication Non-Verbal Communication Competence for People in the village of Mekarmukti, West Bandung". This extension activity was conducted to the community in the village of Mekarmukti, district. West Bandung. Community Service Activities has the purpose to produce the following outcomes: 1) Providing concrete knowledge and insight about non-verbal communication and its current development to the community in Mekarmukti Village, West Bandung Regency; 2) Providing comprehensive knowledge and insight on non-verbal communication concepts, as well as good communication tips. Method of PKM implementation conducted in this extension activity is ice breaking method; lecture method; and feedback collection methods.